Structure-property relations of ferroelectric Pb(Zr0.52Ti0.48)O3-(Bi3.25La0.75)Ti3O12 ceramics - Thongmee N. (2014)
Ceramics with formula (1 - x)Pb(Zr0.52Ti0.48)O3-x(Bi3.25La0.75)Ti3O12 (when x = 0, 0.1, 0.3, 0.5, 0.7, 0.9, 1.0) were prepared by a solid-state mixed-oxide method and sintered at 1150 °C for 4 h. All samples had densities at least 95% of theoretical values. Phase analysis using X-ray diffraction indicated the existence of BLT - as well as PZT - based solid solutions with corresponding lattice distortion. Scanning electron micrographs of ceramic surfaces showed a plate-like structure in BLT-rich phase while the typical grain structure was observed for PZT-rich phase. Ferroelectric measurements of these samples showed that addition of small amounts of BLT into PZT increased coercive field and remanent polarization to about 18 kV/cm and 12.5 μC/cm2, respectively. Further increasing the amount of BLT in PZT degraded the ferroelectric properties of the ceramics. This behavior was in agreement with their microstructures and dielectric properties. © 2007 Elsevier B.V. All rights reserved.